Conceptualization and measurement of health for adults : use of hypnotic and anxiolytic drugs - Kamberg, Caren J., 1946-; Wells, Kenneth B., 1948-; Brook, Robert H. (Robert Henry), 1943-; Goldberg, George A., 1941-; Lohr, Kathleen N., 1941-; Rand Corporation; United States. Department of Health and Human Services (Santa Monica, CA : RAND, 1982)
Use of hypnotic and anxiolytic drugs is an issue of national importance. The Health Insurance Study (HIS) used data on the prevalence and adverse consequences of use to investigate the effect of different levels of health insurance on health and the quality of medical care. Consumption of these drugs was chosen because of their widespread use and the possibility of affecting possible adverse consequences by good medical care. This volume reviews pertinent drug use literature, outlines HIS methods for measuring the prevalence and intensity of use, discusses results from the HIS enrollment population, and lists criteria for acceptable quality of care for persons presenting with complaints associated with the prescription of these drugs. Illustrative findings include: (1) up to 3 and 18 percent of HIS participants were hypnotic or anxiolytic drug users, respectively; (2) women used more drugs than men; and (3) impact from their use was lowest among persons who took them least frequently.
"March 1982."
Includes bibliographical references (p. 81-86).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Drug utilization -- United States; Drugs -- Prescribing -- United States; Drugs -- Side effects; Hypnotics; Medical care -- United States -- Evaluation; Sedatives; Anti-Anxiety Agents; Data Collection -- methods; Hypnotics and Sedatives; Quality of Health Care -- United States